A longitudinal study of fatty acid profiles, macronutrient levels, and plasmin activity in human milk - Meng, Fanyu; Uniacke-Lowe, Therese; Lanfranchi, Elisa; Meehan, Grainne; O'Shea, Carol-Anne; Dennehy, Theresa; Ryan, Anthony C.; Stanton, Catherine; Kelly, Alan L. (Frontiers in Nutrition, 2023)
Introduction Human milk provides nutrients essential for infant growth and health, levels of which are dynamic during lactation. Methods In this study, changes in macronutrients, fatty acids, and plasmin activities over the first six months of lactation in term milk were studied. Results There was a significant influence of lactation stage on levels of protein and plasmin activities, but not on levels of fat and carbohydrate in term milk. Concerning fatty acids in term milk, levels of caproic acid and α-linolenic acid increased significantly (p < 0.05), whereas those of arachidonic acid and docosahexaenoic acid decreased, in the six months after birth. Significant impacts of maternal pre-pregnancy BMI and infant gender on fatty acid profiles were also found. Multivariate statistical analysis showed that protein level, plasmin activity, and several fatty acids (α-linolenic acid, lignoceric acid, and docasadienoic acid) contributed strongly to discrimination of milk from different lactational stages. Discussion The study demonstrates that not all but some fatty acids were influenced by lactation, whereas protein and protease levels showed clear decreasing trends during lactation, which may help in understanding the nutritional requirements of infants.